O SINTOMA COMO LINGUAGEM: QUANDO O CORPO FALA O QUE A PALAVRA SILENCIA1 - PARISE, LUÍGGI SALLA; FERRETTI, MURILO; METZ, ENZO GARZELLA; BORTOLINI, LUIZ MÁRIO CAVALHEIRO; MAYER, LUCAS CANDIDO; SPANANBERG, JOÃO PEDRO SCHMIDT; MAI, JONATAS STEIGER; GROSS, CAROLINA BALDISSERA (Salão do Conhecimento, 2025)
O SINTOMA COMO LINGUAGEM: QUANDO O CORPO FALA O QUE A PALAVRA SILENCIA1